Table olives: a natural source of health-promoting bioactive nutrients and probiotics - Peres C.; Peres C.M.; Moreira L.; Alves M.; Maricato J.; Xavier Malcata F. (Present and future of the Mediterranean olive sector, 2013)
A new generation of natural and healthy foods has been on the rise – and fermented olives are part of that new trend. Concerted public health policies triggered by budgetary restrictions will require investment on prevention rather than bearing – especially as the human life expectancy is becoming longer and longer; and the aforementioned types of foods are nuclear vectors of this strategy as applied to the Mediterranean countries. Some of the components of the olive fruit may by itself function as prebiotics, viz. dietary fibers (with beneficial effects toward prevention of several pathologies), besides such nutraceuticals as essential fatty acids (with anti-cancer features) and antioxidant sterols, polyphenols and glycosides (with general anti-ageing activities). Moreover, some of the adventitious lactic acid bacteria of table olives apparently can survive passage through the gastrointestinal tract – and fully i.e. they resist digestion and even survive in the gut, so they have a chance to act against pathogens installed therein ward showing probiotic capacities. Production of fermented olives with selected (wild) probiotic bacteria therefore constitutes indeed a new avenue to enrichment of the existing olive-based product portfolio, by generating a new food containing probiotics aimed at improving consumers’ health without hampering its original sensory characteristics of that have accounted for their success so far.
International Seminar: Present and Future of the Mediterranean Olive Sector, 2012/11/26-28, Zaragoza (Spain)